Konsep Rumah Tangga Berkeadilan Gender dalam Perspektif KH. Abdurrahman Wahid - Anwar, Khairul; Solihah, Siti Darma Mar'atus; Nafsiyah, Nafsiyah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
A harmonious household is the dream of every couple. This study aims to analyze the role of KH. Abdurrahman Wahid in building family life and analyzing the concept of household in the perspective of KH. Abdurrahman Wahid's gender. This type of research is library research using a qualitative research approach. The object of this research is the concept of a good household which is analyzed through Gus Dur's gender perspective. This study uses two sources of data, namely primary data and secondary data. The results of the discussion show that the concept of a gender-equitable household in Gus Dur's perspective is a household concept that prioritizes the principles of equality, interdependence and justice. In a household, each individual must respect each other's differences. There are at least three important points that can be taken as a reference in building a gender-equitable household. First, respect each other both husband and man. Second, a husband must help his wife's domestic work. Third, as parents, especially fathers, they must free their children to make their own life choices.